2013
DOI: 10.1108/jica-06-2013-0016
|View full text |Cite
|
Sign up to set email alerts
|

Integrated services for women through a One Stop Shop: a realist review

Abstract: Purpose – One Stop Shops (OSSs) are a model of integrated delivery, where a range of needs are met in one place through a bespoke, person-centred service that works across organisational and sectoral boundaries. Third Sector Organisations provide OSSs for women in the criminal justice system and whilst they are shown to be effective in meeting complex needs, how this effectiveness is generated needs explaining. The purpose of this paper is to set out a preliminary framework for explaining their effectiveness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Integrated delivery of services among the 'third' or non-government sector is recognised as vital for achieving personcentred care and service (Hardwick, 2013), although it is not without its challenges associated with protection of 'territory' and competition for funding (Milbourne, 2009). It was evident that meeting the needs of disadvantaged jobseekers required enabling them to access a wide range of supporting and intermediate services concerned not only with vocational assistance but also with other social, health and welfare needs.…”
Section: Implications For Policymentioning
confidence: 99%
“…Integrated delivery of services among the 'third' or non-government sector is recognised as vital for achieving personcentred care and service (Hardwick, 2013), although it is not without its challenges associated with protection of 'territory' and competition for funding (Milbourne, 2009). It was evident that meeting the needs of disadvantaged jobseekers required enabling them to access a wide range of supporting and intermediate services concerned not only with vocational assistance but also with other social, health and welfare needs.…”
Section: Implications For Policymentioning
confidence: 99%
“…A number of studies have shown the positive effects of the operation of integrated public services in one-stop integrated service model in UK (Hardwick, 2013) and other European counties (European Commission, 2013), so also in Asian countries (Hoque & Sorwar, 2015). Not only does it operate well, these studies show that the integrated public service model is even growing very rapidly and positively.…”
Section: Objective Conditionsmentioning
confidence: 94%
“…Not only does it operate well, these studies show that the integrated public service model is even growing very rapidly and positively. The response and acceptance of society are increasingly widespread, as shown by integrative service segmentation in the UK, which has focused on women groups (Hardwick, 2013). In a number of European countries, the growing literature on service integration has documented several advantages of well designed integrated approaches, such as tailor-made, flexible and responsive policy options; cost effectiveness and efficiency by sharing knowledge, expertise and resources across cooperating actors; capacity building and innovation, etc., along with considerable challenges in how to reach these outcomes (McQuaid, 2010).…”
Section: Objective Conditionsmentioning
confidence: 99%
“…This alters the behaviour of participants, which leads to outcomes (O). 18 As it has for other evaluations of holistic interventions, 19 the use of a realist approach will help to expose the multiple resources delivered under the umbrella of ‘advice services’, the ways that these may be employed in different contexts, and how these generate different outcomes.…”
Section: Methods and Analysismentioning
confidence: 99%